Procedura zatrzymania sprawcy jako element wykonywania zadań publicznych z zakresu przeciwdziałania przemocy domowej - Czerwińska, Agata (Studia Prawa Publicznego, 2025)
Detaining a perpetrator of domestic violence is an element of the domestic violence prevention system, which can realistically guarantee the safety of a person affected by domestic violence. Domestic violence is a phenomenon that threatens the health and safety of the victim of domestic violence and violates their sovereignty. The unbroken cycle of violence may be associated with the escalation of the phenomenon, which involves a threat to the life of the victim of such violence. For this reason, the legislator has defined the duties of police officers with regard to counteracting domestic violence and isolating the perpetrator from the victim. The implementation of legal obligations in this area is associated with the appropriate conduct from police officers. This should be preceded by an appropriately conducted assessment of the factual situation, which is a necessary condition for effective combating of the phenomenon of domestic violence. Procedural or preventive detention by police officers can effectively guarantee the safety of the injured person, but it is also associated with consequences for the perpetrator of domestic violence. The article therefore presents the praxeological aspects of detaining the perpetrator and the conditions for applying emergency isolation measures, such as a restraining order imposed on the perpetrator restricting them from approaching the dwelling occupied together with the victim and their immediate surroundings, an order to immediately leave this shared home, and a ban on contact or a ban on approaching or a ban on entering the refuge facility. These are legal measures available to police officers, which can effectively break the cycle of violence and constitute the first step towards ensuring the victim’s safety and providing them with support within the framework of crisis intervention.